Mapping the current state of financial inclusion and its impact on economic growth in the MENA region - Chehayeb, Rabab Jaber; Taher, Hanadi (Nurture, 2024)
Purpose: This study aims to provide a comprehensive descriptive analysis of financial inclusion levels in the MENA (Middle East and North Africa) region and its impact on economic growth indicators. Design/Methodology/Approach: Utilizing panel data regression models, including Fixed Effects and Random Effects, the research assesses how financial inclusion influences economic growth. Findings: The results reveal that financial inclusion has a notable negative impact on economic growth in the MENA region, largely attributed to ongoing conflicts and political instability that disrupt economic activities. Additionally, variations in financial regulations and banking practices across the region complicate the assessment of financial inclusion’s effects on growth. Research Limitations/Implications: This analysis serves as a valuable resource for policymakers, researchers, and practitioners by illustrating the distribution of financial inclusion across MENA countries and its observable effects on economic growth. However, the study is limited by its inability to incorporate key indicators such as religion, digital banking, and corruption levels due to data constraints, and its exclusive focus on banks. Contribution to Literature: This review enhances the literature on financial inclusion by offering an in-depth examination of its current status, providing insights for targeted policy interventions, and assisting financial institutions in identifying growth opportunities and areas needing support. Conclusion: Financial inclusion’s impact on economic growth varies based on measurement methods, leading to discrepancies in studies. Despite strong growth indicators driven by the energy sector in the region, structural rigidities and insufficient financial intermediation have limited the benefits of this growth.